The eyes and ears of conscience: Lessons of encouragement - Kirchhoffer, David G. (The Australasian Catholic record, 2024)
Review(s) of: The eyes and ears of conscience: Lessons of encouragement, by Thomas Ryan (Strathfield, NSW: St Pauls, 2022), pp. 250, paperback, Dollar 29.95.